Answer:
{r:r<17}
Step-by-step explanation:
<em>giv</em><em>en</em><em> </em><em>r+10<-3(2r-3)+6(r+3)</em>
change the < to = to solve the equation
thus, r+10=-3( 2r-3 )+6( r+3 )
r+10= -6r +9 +6r +18
r+10= 9+18
r+10=27
r=27-10
r=17
Answer:
f(2)= -2
g(2)= 12
Step-by-step explanation:
To solve this we use the substitution method. Since f(2) is your variable, we will plug the x-value of 2 into each equation
f(2)= 2(2)^2-5(2)
f(2)=8-10
f(2)= -2
If the same variable is used for both equations then g(x) would be g(2) as well leaving you with
g(x) = 3x^2
g(2)= 3(2)^2
g(2)=12
No it's positive since if you multiply both sides by -1 you will get 5m=20 & m=4
Another method -5m =-20, divide both sides by -5, you will get the same positive m =4
Answer:
= - 9x2+4x+2/4x-2
Step-by-step explanation:
Remove parentheses
its blank we need to find a number
step 1: = -/4x-2 (9x2+4x+2)
step 2: multiply fractions and there is your answer
9x2+4x+2/4x-2
Answer:
10 makes this equation true
Step-by-step explanation:
2x -4 = 16 /+4
2x= 20 /÷2
x= 10
Test
2(10) - 4 = 16
20 - 4 = 16 Correct